Teachers’ Techniques of Assessing English Speaking Skill in Limited Face to Face Learning - Rida Marlenie; Dedi Sofyan; Syafryadin Syafryadin (Edu-Ling: Journal of English Education and Linguistics, 2022)
The objectives of this research were to investigate teachers' techniques in assessing English speaking skill in limited face-to-face learning and the challenges faced by the teachers in implementing English speaking assessment techniques in limited face-to-face learning. This research was qualitative. The subjects of this research were four English teachers of SMPN 5 Bengkulu Tengah. All teachers were observed in their teaching classes, in total there were 14 classes. The data were gathered by using a checklist of observation and interview. The data were analyzed by using the procedures of Miles and Huberman namely; data reduction, display data, and verification and conclusion. The results of this research showed that the teachers used three basic types of speaking assessment; intensive, responsive, and extensive speaking. In the intensive speaking assessment, the techniques used by teachers were; direct response task, read-aloud task, and sentence/dialogue completion task. In the responsive speaking assessment, the techniques used by teachers was questions and answers. In the extensive speaking assessment, the technique used by teachers was oral presentations. The most frequently technique used by the teachers was the read-aloud task. While, the challenges faced by the teachers in assessing speaking skill in limited face-to-face learning were lack of learning time, taking turns learning, declining students’ speaking skill, and difficulty in making students speak. In conclusion, the provisions during limited face-to-face learning and challenges faced by English teachers in assessing English speaking skill in limited face-to-face learning make the speaking skill techniques used by teachers were less varied.